Bunch structure, rudimentary seed size and return fertility of Vitis vinifera L. ‘Sunred Seedless’ as affected by GA3 and GA4+7 thinning treatments - Claassen, Talana (Stellenbosch : Stellenbosch University, 2020)
Thesis (MScAgric)--Stellenbosch University, 2020.